The Functional Sites of “Sites of Memory” in Hungarian-Chinese Bilingual School in Budapest - Liu, Meng (Ethnographica et Folkloristica Carpathica, 2023)
Various aspects of the culture and educational practices of the bilingual school in Budapest’s 15th district, including educational materials, educational drama, and educational rituals, among others, reflect the functional sites of Pierre Nora’s memory sites. These sites are crucial in shaping students’ cultural identities and connecting them to their heritage. By incorporating sites of memory into their school life can help students understand and identify their cultural roots, develop a sense of belonging, and acquire the linguistic and cultural competencies needed for cross-cultural communication. In this paper, based on related memory theories, I explore the definition of functional sites in the sites of memory in schools. Combining the fieldwork in Hungarian-Chinese Bilingual School, it is believed that there are many functional sites of the sites of memory in the bilingual school. The representative functional sites are educational textbooks, dramas, and rituals. This article studies the three main functional sites of memory. It examines how these sites are used in bilingual schools to enhance cultural understanding, promote linguistic and cultural competence, and foster a sense of belonging among students. We will also discuss how these functional sites of memory sites reconstruct or reinterpret Chinese cultural memory.